2017
DOI: 10.1186/s12985-017-0778-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Avian Rotaviruses Group A and D shed by different bird species in Nigeria

Abstract: BackgroundAvian rotaviruses (RVs) cause gastrointestinal diseases of birds worldwide. However, prevalence, diversity, epidemiology and phylogeny of RVs remain largely under-investigated in Africa.MethodsFecal samples from 349 birds (158 symptomatic, 107 asymptomatic and 84 birds without recorded health status) were screened by reverse transcription PCR to detect RV groups A and D (RVA and RVD). Partial gene sequences of VP4, VP6, VP7 and NSP4 for RVA, and of VP6 and VP7 for RVD were obtained and analyzed to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 44 publications
(46 reference statements)
1
31
0
Order By: Relevance
“…Although the results of RVA have already been described globally [12,[23][24][25][26][27][28][29][30], in Brazil, the occurrence, diversity and role of rotavirus in these animals are still poorly studied, considering the large number of present species [4,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of RVA have already been described globally [12,[23][24][25][26][27][28][29][30], in Brazil, the occurrence, diversity and role of rotavirus in these animals are still poorly studied, considering the large number of present species [4,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis showed a high sequence identity of the pigeon isolate to a rotavirus virus strain fox-wt/ITA/288356/2011/G18P[ 17 ] isolated from a red fox, and avian rotavirus strains AROVP1 (KT934648) isolated from a spotted dove and RVA/pigeon-tc/JPN/PO-13/1983/G18P[ 17 ] from a healthy feral pigeon ( Fig 5 ). The NSP4 segment belongs to the E19 genotype first described in this fox [ 20 ] and subsequently reported from avian samples in Nigeria [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…NSP4 is not usually conserved between mammals and birds, with homology calculated at 32–35% for PO-13 and selected mammalian viruses [ 18 ]. Although first described in a mammalian isolate, investigation of birds in farms and live bird markets in Nigeria suggest that G18-P[ 17 ]-[I4]-E19 may be a common genotype of pigeon RVAs [ 13 ], further supporting an avian origin for this isolate. The potential for the virus described here to cross species barriers is unknown; to date no disease has been recognised in species other than Columba livia , but further investigation of its cross- species pathogenicity may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of astroviruses clustered ANV and CAstV in two different groups, and each of them was sub-grouped with the NT sequences of the RNA polymerase gene from isolates originating in North-America and Asia, providing a resource to determine the global distribution of these viruses. The ARtV analyzed in this study showed a close phylogenetic relationship with isolates from the United States, Peru, South Korea, Ireland, Germany, Nigeria, and Brazil, particularly in the length of the branches in the phylogenetic tree, which may confirm the complete distribution of the virus around the world (JINDAL et al, 2010;JINDAL et al, 2014;FUJII et al, 2016;PAULY et al, 2017). Coronaviruses such as IBV are some of the most widely distributed enteric viruses in Brazil and have attracted special interest from the poultry industry due the economic losses caused by its impact on the health of birds (CAVANAGH 2007;SEGER et al, 2016;HUTTON et al, 2017).…”
Section: Phylogenetic Analysissupporting
confidence: 63%